2013
DOI: 10.1002/cbin.10197
|View full text |Cite
|
Sign up to set email alerts
|

Acetazolamide triggers death inducing autophagy in T‐47D breast cancer cells

Abstract: The inhibitory effects of acetazolamide on the growth and proliferation of epithelial breast cancer cells (T-47D) were investigated. Analysis of morphological changes indicated little apoptosis in T-47D cells incubated with acetazolamide, according to data from flow cytometry, DNA laddering, and expression of AIF. However, an increase in caspase-3 activity was detected in cells. This was concomitant with an increase in DFF45/DFF40 ratio leading to inhibition of caspase-3 activity, DNA fragmentation and progres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 37 publications
3
17
0
Order By: Relevance
“…Both AZ and SFN have been reported to modulate individually Akt signalling in T-47D breast cancer cells and colon adenocarcinoma Caco2 cell [41,31]. Here we found that downregulation of the Akt signalling protein was correlated with induced expression of cell cycle inhibitors p21, p27, reduced cyclin D1, PARP, and caspase-3 cleavage, further supporting the targeting of the Akt signalling pathway by the AZ+SFN combination.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Both AZ and SFN have been reported to modulate individually Akt signalling in T-47D breast cancer cells and colon adenocarcinoma Caco2 cell [41,31]. Here we found that downregulation of the Akt signalling protein was correlated with induced expression of cell cycle inhibitors p21, p27, reduced cyclin D1, PARP, and caspase-3 cleavage, further supporting the targeting of the Akt signalling pathway by the AZ+SFN combination.…”
Section: Discussionsupporting
confidence: 73%
“…Using our in vitro and in vivo models, we showed that growth of the tumors was significantly reduced by the AZ+SFN combination, although, the single agent SFN alone still showed an appreciable strong antitumor efficacy in the xenografted mice. Both AZ and SFN have been shown to induce apoptosis in human Caco2 and breast cancer cells and decrease pro-survival Akt phosphorylation [41,31]. Furthermore, SFN alone showed a downregulation tendency of both basal and p-Akt expression in ovarian cancer cells [45].…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, apoptosis induction was detected in caspase 3 defective MCF7 cells ( Figure 2 ). Recently, caspase-independent forms of BA-induced cell death were discussed [ 31 ]. Consistent with this result, Lou et al suggested caspase-independent apoptosis induction by CAIX shRNA [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…When AIF is released into the cytosol, it triggers caspase-independent apoptotic death via DNA fragmentation (Candé et al, 2002). In fact, in MDA-MB-468 treated cells, in addition to the increased expression level of bcl2 and its effects on the calcium-dependent lysosomal death, the caspase-independent apoptotic death, induced by AIF, (AIF dependent apoptosis) was also another auxiliary mechanism that helps calcium ions to induce cell death (Mohammadpour et al, 2014). …”
Section: 0 Discussionmentioning
confidence: 99%